Distribution of Malocclusion Traits among Orthodontic Patients in a Tertiary Care Center of Western Nepal - Halwai, Hemant Kumar; Gautam, Vanita (Orthodontic Journal of Nepal, 2017)
Objectives: To determine the pattern of distribution of dental malocclusion in a sample of Nepalese orthodontic patients in Western Nepal. Materials & Method: A sample consisted of 200 study casts of patient who visited Department of Orthodontics, UCMS, Bhairahawa who had never undergone orthodontic treatment previously. The total sample size was divided into male and female groups, age was divided into 3 groups: 8-11 years, 12-17 years, and 18-36 years. All data was recorded and analyzed with SPSS software version 22. Result: Among the total 200 casts examined; the distribution of malocclusion according to Angle’s classification was: Class I malocclusion in 101(50.5%), Class II malocclusion in 90(45%) sample and Class III in 9(4.5%) samples. Conclusion: Angle’s Class I malocclusion was the most prevalent malocclusion among orthodontic patients visiting UCMS College of Dental Surgery.